(untitled) (Iraqi National Journal of Earth Science (INJES), 2026)
The research deals with the hydrological analysis of the Wadi Bagal basin in Badoosh, Nineveh Governorate. It is considered one of the seasonal flow basins. The study includes analysis of the natural characteristics and also conducts an analysis of the hydrological characteristics using the American Soil Conservation Model– (SCS – CN) (Soil Conservation Services) to obtain permeability values (CN) (Curve Number) by integrating landuse, vegetation, soil status and hydrological soil group layers. Then getting the maximum potential coefficient values for retaining water after the surface runoff (S). In addition to obtaining the values of the inital extraction coefficient (Ia). The Baghal Basin is located in the northwestern part of Iraq in Nineveh Governorate between latitudes (36°27’50" -36°19’00") north and longitudes (42°38’15" -42°58’50) east with area of (320) km2. The results show that the values of (CN) range between (62- 97), which is higher than the median value of (50) indicating the possibitity of water migration. As for the values of (S), they range between (39- 59), which all of them are below the median value of (254) indicating that the basin is normal in retaining water after the start of the water flow. As for the values of (Ia), they range between (7.3 – 14.6) below the median value of (50.8) indicating that the basin tends to have the possibility of water flow.